Hermeneutics of the Syahādah in Kiai Sa‘īd’s Ta‘līm al-Mubtadi’īn fī ‘Aqā’id al-Dīn: A Reflective Theological Analysis - Abdul Hanan (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2025)
This study explores Kyai Sa’īd’s unique hermeneutical approach in his seminal work, “Ta’līm al-Mubtadi’īn fī Aqāid al-Dīn,” focusing on the syahadah (Islamic declaration of faith). Kyai Sa’īd’s integration of regional language (Javanese Pegon) and his nuanced response to diverse religious and social dynamics of his era underpin the analysis. The research employs a qualitative analysis of Kyai Sa’īd’s interpretative techniques, examining his selective engagement with Qur’anic verses and the integration of jurisprudential terms. The study contextualizes Kyai Sa’īd’s work within the broader socio-political framework of his time, drawing on the principles of Hans-Georg Gadamer’s Hermeneutics to understand the historical influences on his exegesis. Kyai Sa’īd’s exegesis demonstrates a reflective theological approach, categorized as ‘tafsīr bi al-ra’yī’ (interpretation based on opinion). His selective focus on parts of verses and the infusion of jurisprudential terminology illustrate a strategy to make the text accessible and relatable to his contemporary audience. His interpretations reveal an underlying objective to balance theological depth with practical applicability, addressing both philosophical and legal aspects of Islamic creed. Kyai Sa’īd’s work transcends traditional exegesis, acting as a testimony to the political, economic, and cultural upheavals of his time. His approach showcases an imaginative leap in understanding, framing Qur’anic interpretation within the syahadah’s context. This method reflects a deep engagement with the socio-political and religious dynamics of his era, suggesting a nuanced theological response to these challenges.